The study of size effect on aluminium - silicon contacts characteritics - 245695 Mahanum Abdullah Sadali; Zulkafli Othaman,lcsupervisor; Fakulti Sains (2005)
Project Paper (Sarjana Muda Sains Industri (Fizik Bahan)) - universiti Teknologi Malaysia, m2005